2021
DOI: 10.1093/scan/nsab041
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between childhood stress and distinct stages of dynamic behavior monitoring in adults: neural and behavioral correlates

Abstract: Childhood adversity is a major risk factor for emotional and cognitive disorders later in adulthood. Behavior monitoring, one of the most important components of cognitive control, plays a crucial role in flexible interaction with the environment. Here, we test a novel conceptual model discriminating between two distinct dimensions of childhood adversity (i.e., deprivation and threat) and examine their relations to dynamic stages of behavior monitoring. Sixty young healthy adults participated in this study usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 92 publications
2
11
0
Order By: Relevance
“…This effect, to some extent, was in line with previous studies that abused children tended to avoid negative information shown as biased attention away from threat (Pine et al, 2005), and as decreased activation of amygdala to negative stimuli (Puetz et al, 2016). Meanwhile, the current result also echoed with one previous study from our own lab that childhood abuse rather than neglect was associated with blunted motivational evaluation of self-inflicted errors among healthy young males (Wu et al, 2021). Furthermore, our mediation analysis showed that childhood abuse predicted blunted HR response through blunted processing to negative stimuli.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This effect, to some extent, was in line with previous studies that abused children tended to avoid negative information shown as biased attention away from threat (Pine et al, 2005), and as decreased activation of amygdala to negative stimuli (Puetz et al, 2016). Meanwhile, the current result also echoed with one previous study from our own lab that childhood abuse rather than neglect was associated with blunted motivational evaluation of self-inflicted errors among healthy young males (Wu et al, 2021). Furthermore, our mediation analysis showed that childhood abuse predicted blunted HR response through blunted processing to negative stimuli.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, threat, referring to interpersonal violence exposures of actual or threatening harm (e.g., physical, emotional and sexual abuse), influences the development of cortico-limbic circuits that underlie fear learning and salience processing; deprivation, referring to the lack of expected cognitive and social inputs as in the case of physical and emotional neglect, influences the development of the association cortex, which in turn might produce difficulties in multiple domains in executive functioning (Sheridan & McLaughlin, 2014; Teicher & Samson, 2016; Teicher et al, 2016). Interestingly, there is some empirical evidence suggesting that childhood experiences of threat but not deprivation are associated with blunted sympathetic and cortisol responses to acute stress (Busso et al, 2017), as well as with blunted salience processing in terms of self-inflicted error and fear (Wu et al, 2021; Machlin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is similar in nature to that of Lackner et al (2018) , who found that adolescents in a high trauma group (i.e., those who had more than four adverse childhood experiences) had greater error-related activity when compared to medium and low trauma groups. In a parallel manner, Wu et al (2021) found that a greater self-reported severity of childhood adversity experiences, including severe domains of abuse and neglect, related to a larger ERN in adult males. It is interesting to note that Lackner et al (2018) assessed and did not find a relationship between the frequency of traumas and error-related activity.…”
Section: Discussionmentioning
confidence: 80%
“…One study found that, among adolescents, higher numbers of adverse childhood experiences related to a larger ERN ( Lackner et al, 2018 ). Additionally, a recent investigation by Wu et al (2021) revealed that a greater severity of childhood adversity experiences (e.g., childhood abuse and neglect) was associated with a more negative ERN in a sample of adult males.…”
Section: Introductionmentioning
confidence: 97%
“…In a recent study, we examine the relationship between interpersonal dependent and non‐interpersonal stressful life events and the ∆ERN in a sample of child and adolescent females, finding that more frequent interpersonal dependent stressors predict a larger ∆ERN (Mehra & Meyer, in press). Previous work found that higher numbers of adverse childhood experiences related to a larger ERN (Lackner et al, 2018; Wu et al, 2021) and one study found that social‐evaluative stress during early adolescence was related to an enhanced ERN (Banica et al, 2021). Moreover, two studies have found that the ERN interacts with stressful events to predict changes in anxiety prospectively (Banica et al, 2020; Meyer, Danielson, et al, 2017).…”
Section: Factors That Shape the Ernmentioning
confidence: 98%